Studying laser radiation effect on steel structure and properties - Gazaliev A. M. Arstan Maulenovich; Melnikov A. G. Alexander Grigorievich; Lobankova O. V. Olga Vladimirovna; Zykov I. Yu. Iliya Yurievich; Kvon S. S. Svetlana Sergeevna; Filippova T. S. Tatjyana Sergeevna (2016, 2016)
There was studied the effect of laser radiation on the structure and properties of annealed and tempered steel with different content of carbon. For surface hardening there was used a laser complex equipped with Nd: YAG pulse laser with power density up to 30 kW/?m2. As a result of the carried-out studies there were calculated characteristics of laser, steel microstructure and properties.